Evaluation of two short standardised regimens for the treatment of rifampicin-resistant tuberculosis (STREAM stage 2): an open-label, multicentre, randomised, non-inferiority trial. Issue 10366 (26th November 2022) - Goodall, Ruth L; Meredith, Sarah K; Nunn, Andrew J; Bayissa, Adamu; Bhatnagar, Anuj K; Bronson, Gay; Chiang, Chen-Yuan; Conradie, Francesca; Gurumurthy, Meera; Kirenga, Bruce; Kiria, Nana; Meressa, Daniel; et al.
Summary: Background: The STREAM stage 1 trial showed that a 9-month regimen for the treatment of rifampicin-resistant tuberculosis was non-inferior to the 20-month 2011 WHO-recommended regimen. In STREAM stage 2, we aimed to compare two bedaquiline-containing regimens with the 9-month STREAM stage 1 regimen. Methods: We did a randomised, phase 3, non-inferiority trial in 13 hospital clinics in seven countries, in individuals aged 15 years or older with rifampicin-resistant tuberculosis without fluoroquinolone or aminoglycoside resistance. Participants were randomly assigned 1:2:2:2 to the 2011 WHO regimen (terminated early), a 9-month control regimen, a 9-month oral regimen with bedaquiline (primary comparison), or a 6-month regimen with bedaquiline and 8 weeks of second-line injectable. Randomisations were stratified by site, HIV status, and CD4 count. Participants and clinicians were aware of treatment-group assignments, but laboratory staff were masked. The primary outcome was favourable status (negative cultures for Mycobacterium tuberculosis without a preceding unfavourable outcome) at 76 weeks; any death, bacteriological failure or recurrence, and major treatment change were considered unfavourable outcomes. All comparisons used groups of participants randomly assigned concurrently. For non-inferiority to be shown, the upper boundary of the 95% CI should be less than 10% in both modified intention-to-treat (mITT) and per-protocol analyses, with prespecified tests for superiority done if non-inferiority was shown. This trial is registered with ISRCTN, ISRCTN18148631. Findings: Between March 28, 2016, and Jan 28, 2020, 1436 participants were screened and 588 were randomly assigned. Of 517 participants in the mITT population, 133 (71%) of 187 on the control regimen and 162 (83%) of 196 on the oral regimen had a favourable outcome: a difference of 11·0% (95% CI 2·9–19·0), adjusted for HIV status and randomisation protocol (p<0·0001 for non-inferiority). By 76 weeks, 108 (53%) of 202 participants on the control regimen and 106 (50%) of 211 allocated to the oral regimen had an adverse event of grade 3 or 4; five (2%) participants on the control regimen and seven (3%) on the oral regimen had died. Hearing loss (Brock grade 3 or 4) was more frequent in participants on the control regimen than in those on the oral regimen (18 [9%] vs four [2%], p=0·0015). Of 134 participants in the mITT population who were allocated to the 6-month regimen, 122 (91%) had a favourable outcome compared with 87 (69%) of 127 participants randomly assigned concurrently to the control regimen (adjusted difference 22·2%, 95% CI 13·1–31·2); six (4%) of 143 participants on the 6-month regimen had grade 3 or 4 hearing loss. Interpretation: Both bedaquiline-containing regimens, a 9-month oral regimen and a 6-month regimen with 8 weeks of second-line injectable, had superior efficacy compared with a 9-month injectable-containing regimen, with fewer cases of hearing loss. Funding: USAID and Janssen Research & Development.